1998
DOI: 10.1523/jneurosci.18-03-01161.1998
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Correlated Noise in the Discharge of Neurons in Motor and Parietal Areas of the Primate Cortex

Abstract: We analyzed the magnitude and interneuronal correlation of the variability in the activity of single neurons that were recorded simultaneously using a multielectrode array in the primary motor cortex and parietal areas 2/5 in rhesus monkeys. The animals were trained to move their arms in one of eight directions as instructed by a visual target. The relationship between variability (SD) and mean of the discharge rate was described by a power function with a similar exponent ( approximately 0.57), regardless of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
298
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(338 citation statements)
references
References 53 publications
35
298
5
Order By: Relevance
“…We detected an overall positive correlation, which was to a large degree independent of sensory and motor parameters and variables relating to the animal's performance and motivation, providing an instance of residual noise correlation in the cortex that cannot be accounted by behavioral factors. Correlated noise between neurons recorded from the same electrode was in the same broad range as in other cortical areas of the monkey (Gawne and Richmond 1993;Lee et al 1998;Maynard et al 1999;Zohary et al 1994) as well as the frontal cortex of the rat (Jung et al 2000). It is difficult however to directly compare these values as sensory and motor variations in each trial may have a higher impact in other cortical areas.…”
Section: Trial-to-trial Covariationsmentioning
confidence: 91%
See 2 more Smart Citations
“…We detected an overall positive correlation, which was to a large degree independent of sensory and motor parameters and variables relating to the animal's performance and motivation, providing an instance of residual noise correlation in the cortex that cannot be accounted by behavioral factors. Correlated noise between neurons recorded from the same electrode was in the same broad range as in other cortical areas of the monkey (Gawne and Richmond 1993;Lee et al 1998;Maynard et al 1999;Zohary et al 1994) as well as the frontal cortex of the rat (Jung et al 2000). It is difficult however to directly compare these values as sensory and motor variations in each trial may have a higher impact in other cortical areas.…”
Section: Trial-to-trial Covariationsmentioning
confidence: 91%
“…Functional classes of neurons have been previously defined based on their firing rate properties (Taira and Georgopoulos 1993), and differences in terms of their correlated discharges have been identified; however, these differences involved the relationship between signal and noise correlation rather than the actual value of noise correlation that we report here (Lee et al 1998). The higher discharge synchronization between FS units that we report in this study is consistent with intracellular recordings suggesting that nearby interneurons form a tight network of electrotonic synapses and synchronize their firing with millisecond precision (Beierlein et al 2000;Gibson et al 1999).…”
Section: Short Scale Synchronizationmentioning
confidence: 92%
See 1 more Smart Citation
“…This variability is thought to limit the capacity of individual neurons to transmit information (9). Furthermore, variability is often correlated among neurons, and thus, it cannot be completely removed by averaging the population response (9)(10)(11)(12). Recent experimental studies have examined the secondorder statistics of neural responses across a variety of species, cortical areas, tasks, and stimulus and/or attentional conditions (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Even the responses of nearby neurons located within the same functional column, which encode the same stimulus property, exhibit a high degree of heterogeneity (1)(2)(3)(4)(5). In primary visual cortex (V1), for instance, it has been reported that neurons tuned to the same stimulus orientation exhibit a high degree of variability in their strength of orientation selectivity, peak response, and baseline activity (1,2).…”
mentioning
confidence: 99%